Interobserver variation in the diagnosis and grading of dyskaryosis in cervical smears: specialist cytopathologists compared with non-specialists. Issue 6 (June 1994) - O'Sullivan, J P; Ismail, S M; Barnes, W S; Deery, A R; Gradwell, E; Harvey, J A; Husain, O A; Kocjan, G; McKee, G; Olafsdottir, R
Abstract : AIMS–To compare the assessment of dyskaryosis in cervical smears made by specialist consultant cytopathologists and consultant general histopathologists. METHODS–One hundred and ten cervical smears were circulated to 10 observers from five district general hospital histopathology departments and five major departments of cytopathology. Their responses were analysed by five consultant general histopathologists and five consultant specialist cytopathologists. In 54 of the 110 cases, the histology of a corresponding cervical biopsy specimen was compared with the smear assessments. RESULTS–Specialist cytopathologists were more consistent than non-specialists when diagnosing and grading dyskaryosis. They chose the higher grades of dyskaryosis more frequently than the non-specialists. The cytopathologists recommended referral for colposcopy more frequently, but if they asked for a repeat smear, they wanted it done within three months more frequently than the histopathologists. The specialists were more frequently in agreement with the biopsy grade of intra-epithelial neoplasia than the non-specialists, whose smear diagnoses tended to underestimate the severity of the histopathological abnormality. CONCLUSIONS–This study has shown major differences between specialist and non-specialist cytopathologists in the diagnosis and grading of cervical smears and in the recommended management of patients with abnormal smears. These differences may result in uneven clinical management of women with smear abnormalities. It is therefore important to explore possible strategies for standardising the reporting of cervical smears, such as centralisation of screening services, accreditation in cytopathology for non-specialist consultants, and the value of participation in external quality assessment schemes.